Material difference : modernism and the allegories of discourse - Melaney, William D. (Text (Rodopi (Firm)), 2012)
Material Difference: Modernism and the Allegories of Discourse argues that deconstruction can be employed in conjunction with the historically-oriented approach to cultural experience that is favored by Critical Theory. The two discourses that inform this comparative study situate Modernism between evolving traditions that begin with Hegel and Nietzsche, leading on to Adorno's commitment to philosophical aesthetics and Derrida's concern for writing (écriture). Interrelated discussions of eight major authors, working in four different languages, are presented to show how allegorical Modernism.